21-356 Lecture 8

# x 1 1 x y 1 2f 2 0 0 y 0 o x2 y 2

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ) y o x2 + y 2 (1 + x) # 1 % % lim = lim = 0. (x,y )%(0,0) (x,y )%(0,0) x2 + y 2 x2 + y 2 Note that if we had to calculate the limit y (1 + x) # 1 , x2 + y 2 (x,y )%(0,0) lim then we would need Taylor’s formula of order m = 2 at (0, 0), &quot;f &quot;f (0, 0) (x # 0) + (0, 0) (y # 0) &quot;x &quot;y 1 &quot;2f 1 &quot;2f 2 + (0, 0) (x # 0) + (0, 0) (x # 0) (y # 0) + 2 (2, 0)! &quot; x (1, 1)! &quot; x&quot; y * + 1 &quot;2f 2 + (0, 0) (y # 0) + o x2 + y 2 . 2 (0, 2)! &quot; y f (x, y ) = f (0, 0) + 20 Wednesday, January 26, 2011 Proof of Taylor’s formula. Step 1: Since x0 &quot; U and U is open, there exists B (x0 , r) \$ U . We prove Taylor’s formula with Lagrange’s reminder, that is, f (x) = ! 0\$|&quot;|&lt;m ! 1 &quot;&quot;f 1 &quot;&quot;f &quot; &quot; (x0 ) (x # x0 ) + (x0 + c (x # x0 )) (x # x0 ) , &quot; !! &quot; x !! &quot; x&quot; |&quot;|=m (6) for all x &quot; B (x0 , r) and where c &quot; (0, 1). Fix x &quot; B (x0 , r), let h := x # x0 and consider the function g (t) := f (x0 + th) deﬁned for t &quot; [0, 1]. By Lemma 21 and Remark 22, we have that N ! &quot;f dg (t) = (x0 + th) hi = (h · &amp;) f (x0 + th) dt &quot; xi i=1 with for all t &quot; [0, 1]. By repeated applications of Lemma 21 and Remark 22, we get that d ( n) g n (t) = (h · &amp;) f (x0 + th) dtn n for all n = 1, . . . , m, where (h · &amp;) means that we apply the operator h · &amp; = h1 &quot; &quot; + · · · + hN &quot; x1 &quot; xN n times to f . By the multinomial theorem, and the fact that for functions in C m partial derivatives commute, &quot; #n &quot; &quot; n (h · &amp;) = h1 + · · · + hN &quot; x1 &quot; xN ! n! &quot; &quot; &quot; = h , !! &quot; x&quot; &quot; multi-index, |&quot;|=n and so d ( n) g (t) = dtn ! &quot; multi-index, |&quot;|=n n! &quot; &quot; &quot; f h (x0 + th) . !! &quot; x&quot; Using Taylor’s formula for g , we get g (1) = g (0) + m!1 ! n=1 1 d ( n) g 1 d(m) g n m (0) (1 # 0) + (c) (1 # 0) n n! dt m! dtm for some c &quot; (0, 1). Substituting, we obtain f (x0 + h) = ! 0\$|&quot;|=m!1 ! 1 &quot;&quot;f 1 &quot;&quot;f (x0 ) h&quot; + (x0 + ch) h&quot; . &quot; !! &quot; x !! &quot; x&quot; |&quot;|=m 21 (7)...
View Full Document

Ask a homework question - tutors are online